Kobiety Konspiracyjnego Wojska Polskiego przed Wojskowym Sądem Rejonowym w Łodzi (1946–1955) - Feder, Karolina (Acta Universitatis Lodziensis. Folia Historica, 2014)
Military regional courts were created on the basis of organizational order number 023/org. announced on 20th of January 1946 by Polish Military Commander-in-Chief marshal Michał Rola-Żymierski. These courts dealt with the cases of civilians, who were under the jurisdiction of Military Courts, and officers of public security, Citizen’s Militia, prison guards and soldiers of interior army. Military Regional Court in Łódź started performing its duties on March 1946 and during the time of its activity it was governed by three bosses: Mikołaj Nippe, Bronisław Ochnio oraz Henryk Andrysiak. The courts, after completing their duty which was breaking underground independence movements, were dissolved on 30th of April 1955. In Military Regional Court in Łódź 8644 people were sentenced. There were 103 women which were judged and belonged to Underground Polish Army. The biggest number of sentences were announced in 1949 (31) whereas in 1951 and 1955 none of the women was judged. The highest penalty, given to women associated with Underground Polish Army, was given to Janina Torczyńska and it was 15 years. Most of the verdicts concerned 4–5 years of imprisonment because most of the women were accused of help not membership of conspiratorial organization.